The Role of Teachers in Accommodating the Learning Needs of Students with Speech Delay in Regular Elementary School Classrooms - Purowati, Maesaroh; Marmoah, Sri; Salimi, Moh (Universitas Sebelas Maret, 2026)
This study aims to describe the implementation of inclusive education and the role of teachers in accommodating the learning needs of students with speech delays in regular elementary school classes. The study used a descriptive qualitative approach with a case study. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results show that inclusive learning is implemented in regular classes with diverse student characteristics. Teachers act as facilitators, motivators, and social-emotional guides by adjusting methods, media, and communication patterns, such as the use of simple language, visual media, and providing additional time. These efforts can increase student participation and confidence. However, there are still obstacles such as limited teacher competence, time, and professional support. It is concluded that the success of inclusive education is highly dependent on teacher readiness and school system support.